Fundamental Motor Skill Delays in Preschool Children With Disabilities: 2012 National Youth Fitness Survey - E. Andrew Pitchford; Willie Leung; E. Kipling Webster (Frontiers Media S.A., 2021)
Delays in fundamental motor skill (FMS) competency have been observed in a variety of children with disabilities. However, evidence of FMS delays is largely limited to small, geographically specific, limitedly diverse, and non-representative samples. The purpose of this study was to examine the association between FMS competency and reported disability status among pre-school children, ages 3-5 years, using the 2012 National Youth Fitness Survey (NYFS). In total, 329 preschool children (49% female; 4.00 ± 0.04 years of age) from the 2012 NYFS completed the Test of Gross Motor Development−2, including 43 preschoolers identified with a disability based on parental report (44% female; 4.20 ± 0.16 years). Associations were examined with logistic regression using sampling weights. Poor FMS competency, defined as gross motor quotient scores ≤ 79, was observed in significantly more children with disabilities (29%) than children without disabilities (10%, OR = 3.5, p = 0.04). While not statistically significant, there was a growing disparity in FMS competency at age 5 (41 vs. 11%) compared to age 3 (15 vs. 9%, OR = 1.80, p = 0.30). The results provide additional evidence for poor FMS competency among pre-school children with disabilities. FMS should be an early part of comprehensive assessments for all children suspected of disability or development delay as it is critical to identify and intervene upon FMS delays before discrepancies can widen.